2019
DOI: 10.1016/j.jtcme.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective potency of some spice herbs, a literature review

Abstract: In recent years, growing attention has been given to traditional medicine. In traditional medicine a large number of plants have been used to cure neurodegenerative diseases such as Alzheimer's disease (AD) and other memory related disorders. Crocus sativus (C. sativus), Nigella sativa (N. sativa), Coriandrum sativum (C. sativum), Ferula assafoetida (F. assafoetida), Thymus vulgaris (T. vulgaris), Zataria multiflora (Z. multiflora) and Curcuma longa (C. longa) were used traditionally for dietary, food additive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 97 publications
0
55
0
Order By: Relevance
“…As edible plant spices, they could make food fragrant, spicy, bitter, sweet and other characteristics. [2,3] Among them, volatile and nonvolatile components played critical roles in flavor characteristics. They were of great significance to determine and evaluate spices.…”
Section: Introductionmentioning
confidence: 99%
“…As edible plant spices, they could make food fragrant, spicy, bitter, sweet and other characteristics. [2,3] Among them, volatile and nonvolatile components played critical roles in flavor characteristics. They were of great significance to determine and evaluate spices.…”
Section: Introductionmentioning
confidence: 99%
“…Although not appearing as a medicinal herb used traditionally, crocus petals are significantly less expensive than stigmas, prompting researchers to examine their potential in treating depression. Thus, a trial comparing the efficacy of petals and stigmas suggests that they are equally effective in the treatment of mild to moderate depression [44,45].…”
Section: Antidepressantmentioning
confidence: 99%
“…Linalool, terpene alco-hol, improved learning and memory in a transgenic mouse model of AD by reduction of the level of inflammation markers [15]. Khazdair et al [16] reported that monoterpenes from various medicinal plants are active constituents with therapeutic potential in disorders associated with neuroinflammation and neurotransmitter deficiency such as AD and depression.…”
Section: Introductionmentioning
confidence: 99%